THU0209 Lymphocyte subsets in biopsy specimen are associated with spontaneous regression of lymphoproliferative disorders in rheumatoid arthritis patients treated with methotrexate. (15th June 2017) - Kameda, T; Izumikawa, M; Inoo, M; Onishi, I; Kurata, N; Nakashima, S; Shimada, H; Ozaki, H; Wakiya, R; Kondo, A; Kadowaki, N; Dobashi, H
Abstract : Background: Patients with rheumatoid arthritis (RA) have a high risk for lymphoproliferative disorders (LPDs). An LPD in a patient treated with methotrexate (MTX) is known as MTX-associated LPD (MTX-LPD), which is classified among immunodeficiency-associated lymphoproliferative disorders (ID-LPD) as "other iatrogenic ID-LPD" in the 2008 World Health Organization Classification of Tumours of Haematopoietic and Lymphoid Tissues (1). We previously reported that MTX is an independent risk factor for LPD onset in Japanese patients with RA (2). In MTX-LPD, MTX withdrawal can result in spontaneous regression of LPD. In addition, limited evidence indicates that Epstein–Barr virus infection is related to spontaneous regression of MTX-LPD. No biomarker has been identified that predicts spontaneous regression of MTX-LPD. Objectives: To identify a biomarker that predicts spontaneous regression of MTX-LPD in RA patients. Methods: We enrolled RA patients from Kagawa Prefecture, Japan, who developed MTX-LPD during the period from June 2010 through December 2016. RA was diagnosed in accordance with the American College of Rheumatology 1987 classification criteria and was treated with disease-modifying antirheumatic drugs, including MTX. The patients were divided into two groups: those followed-up after discontinuation of MTX alone (MTX withdrawal group) and those who received chemotherapy at 1 month or later after MTX discontinuation (chemotherapy group). The following variables were compared between groups: change in peripheral lymphocyte subsets after MTX discontinuation, serum soluble interleukin-2 receptor, and lymphocyte subsets and Epstein–Barr virus–encoded RNAs in a biopsy specimen from a lesion. Results: We enrolled 43 MTX-LPD patients (29 in the withdrawal group and 14 in the chemotherapy group). From among these groups, we selected 32 patients for analysis of changes in peripheral lymphocyte subsets (23 in the withdrawal group and 9 in the chemotherapy group) and 22 for analysis of lymphocyte subsets in a lesion specimen (11 each in the withdrawal group and chemotherapy group). Peripheral lymphocyte counts were significantly higher after MTX discontinuation in the withdrawal group. Analysis of lymphocyte subsets from lesion specimens revealed significantly higher CD8-positive lymphocyte counts in the chemotherapy group than in the withdrawal group. Conclusions: Lymphocyte count differed before and after MTX discontinuation, and a higher CD8-positive lymphocyte count in a lesion specimen was associated with spontaneous regression of MTX-LPD. These findings may help identify a predictive marker for MTX-LPD treatment and management. References: Swerdlow SH, Campo E, Harris NL, Jaffe ES, Pileri SA, Stein H, et al., WHO Classification of Tumours of Haematopoietic and Lymphoid Tissues. IARC Press, Lyon, 2008. Association of higher methotrexate dose with lymphoproliferative disorders onset in rheumatoid arthritis patients. Kameda T, Dobashi H, Miyatake N, Inoo M, Onishi I, Kurata N, Mitsunaka H, Kawakami K, Fukumoto T, Susaki K, Izumikawa M, Nakashima S, Shimada H, Takeuchi Y, Haba R, Mano S, Onishi H, Imataki O, Matsunaga T. Arthritis Care Res (Hoboken). 2014 Sep;66(9):1302–9. Disclosure of Interest: None declared